Stress in Children Whose Parents Suffer from Mental Disorders - Lea Diklić; Marija Krip (Southeastern European Medical Journal, 2024)
It is already a well-known fact how important early life experiences are in shaping an individual's personality, and one of the most important factors that influence a person's psychological development are parenting styles and the attachment that develops between parents and children. Parenting is a complex process that carries with it a great responsibility, and consists of taking care of the child's basic, physiological needs, as well as raising, guiding and encouraging the child's cognitive, emotional and social development. Parenting can be a particularly big challenge for people suffering from mental disorders, and some studies show that children of parents suffering from mental disorders have a higher risk of developing mental disorders compared to the general population. They are at increased risk of experiencing emotional, developmental and social problems. The mentioned difficulties can be caused by biological predispositions, but also by environmental factors. Mental illness of parents can result in less emotional availability of parents to children and insecure forms of attachment, insufficiently adequate way of establishing communication towards the child, weaker ability to recognize the child's needs and in extreme situations can result in increased hostility towards the child, complete neglect, rejection and potential abuse. Numerous social and economic factors associated with the psychiatric illness of the parents can also adversely affect the child's development, and some of the more prominent ones are social stigma towards psychiatric illnesses, which affects not only the sick person but also family members, lack of social support, poverty and difficult access to education and employment. However, for many parents suffering from psychiatric illnesses, children represent a strong motivation for treatment. Providing support to children and parents, education and strengthening social support can significantly reduce the risk of developing psychological disorders in children themselves.